Successful Science-Industry Cooperation in Transition Economy: Some Insights from Polish SMEs Sector - Hanna MIZGAJSKA; Lukasz WSCIUBIAK (Communications of International Proceedings, 2021)
The purpose of the article is to identify factors which favour building successful collaboration between small and medium enterprises in transition economies and research institutions. Adopting a qualitative approach and using multiple case study method, an analysis was performed on three small and medium enterprises from Southern Greater Poland region. The research allows to draw the conclusion that building collaboration with scientific institutions is fostered by the following: involvement of the top management of the enterprise, strengthening inner potential through developing human resources, conducting own R&D and technological modernisation, as well as the use of EU funds. An important factor is also developing the network of personal contacts with research workers and the fact that the enterprise employs people with previous experience of working in public R&D sector. The article makes a contribution to sparse literature concerning collaboration of science and industry in the countries of Central and Eastern Europe. The results achieved may also constitute a set of recommendations for business practitioners and political decision makers responsible for shaping innovative policies in transition economies.
Keywords: Innovation; small and medium-sized enterprises; transition economies; science-industry collaboration